Gymnastic Training and Dynamic Mobilization Exercises Improve Stride Quality and Increase Epaxial Muscle Size in Therapy Horses - de Oliveira, Kátia [UNESP]; Soutello, Ricardo V.G. [UNESP]; da Fonseca, Ricardo [UNESP]; Costa, Ciniro [UNESP]; de L. Meirelles, Paulo R. [UNESP]; Fachiolli, Daniele F. [UNESP]; Clayton, Hilary M. (Elsevier, 2015)
The objective was to evaluate the efficacy of gymnastic training (GYM) and dynamic mobilization exercises (DMEs) on stride length (SL) and epaxial muscle size in therapy horses. Nine cross-bred hippotherapy horses that performed three, 25-minute therapeutic riding sessions per week throughout the study period were randomly assigned to three experimental groups: a control group in which the horses were sedentary with no additional physical activity; a group that performed DMEs; and a group that performed both DMEs and additional GYM including pelvic tilting, backing, turning in small circles, and walking over a raised rail to strengthen the abdominal and pelvic stabilizer muscles. The exercises were performed 3 days per week for 3 months, with evaluations at the start and end of the study. Stride quality was assessed by measuring SL and tracking distance (TD). Epaxial muscle size was monitored by ultrasonographic measurement of m. longissimus dorsi (LD) thickness and m. multifidi (MM) cross-sectional area. Paired t tests were used to compare within groups across time, and between groups were detected using analysis of variance with Tukey post hoc test. When walking at 1.3 m/s, SL and TD at walk increased significantly (P < .05) in horses subjected to GYM. Thickness of LD did not change in any group, but cross-sectional area of MM increased significantly by 3.55 cm2 (DME) and 3.78 cm2 (GYM). It was concluded that GYM training improved stride quality and DME-stimulated MM hypertrophy which has been shown to improve intervertebral joint stability in other species.
Keywords: Dynamic mobilization exercise; Equine; Hippotherapy; Physical training; Therapeutic exercise; Three-dimensional movement